2017
DOI: 10.17507/jltr.0804.24
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Effect of Portfolio and Summative Assessments on EFL Learners' Writing Ability, Anxiety, and Autonomy

Abstract: (2000), whereas in the summative assessment group, the common traditional summative assessment approach was implemented. After the treatment phase, both experimental groups were given another writing section of the PET test and the same anxiety and autonomy questionnaires as the posttests. The analysis of the test scores using two independent-samples t-tests and an analysis of covariance (ANCOVA) revealed that the summative assessment group had a significantly higher post-treatment level of anxiety. Furthermoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In contrast, a focus on teacher-student interaction enhancement is likely to be effective. Portfolio assessment, which enhances teacher-student communication, was found effective in reducing more FLA in comparison with a non-interventional group ( Nosratinia and Abdi, 2017 ). Teacher feedback, feed up, and feed forward ( Zarrinabadi and Rezazadeh, 2020 ) also resulted in a significant reduction in FLA, but the study had no comparison group.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast, a focus on teacher-student interaction enhancement is likely to be effective. Portfolio assessment, which enhances teacher-student communication, was found effective in reducing more FLA in comparison with a non-interventional group ( Nosratinia and Abdi, 2017 ). Teacher feedback, feed up, and feed forward ( Zarrinabadi and Rezazadeh, 2020 ) also resulted in a significant reduction in FLA, but the study had no comparison group.…”
Section: Resultsmentioning
confidence: 98%
“…We found seven features: CMC, student–student communication, teacher-student communication, performance, strategy instruction, counseling and training, and mood boosters. The most common features were related to communication: CMC such as text chat and online forums ( Arnold, 2007 ), student–student interactions such as peer feedback ( Bailey and Cassidy, 2019 ), and teacher-student interaction such as portfolio assessment ( Nosratinia and Abdi, 2017 ). Some interventions included both student–student and teacher-student interactions ( Liao and Wang, 2015 ; Chen et al, 2016 ; Tang, 2016 ), and some had both CMC and student–student/teacher-student communication (e.g., Ku and Chen, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, testing and judging students' learning at every single assessment occasion proved to be highly threatening for them. Accordingly, the use of process-oriented tools like portfolio assessment with timely, more detailed, and motivating feedback, as was the case in the present study, might be beneficial for lowering students' writing anxiety and enhancing their writing self-concept (Nezakatgoo, 2011;Nosratinia & Abdi, 2017;Peterson & McClay, 2010). Hamp-Lyons and Condon (2000) contend that one of the most attractive features of portfolio assessment is "delayed evaluation", giving students and teachers more time for revision and generating a "success now" atmosphere that helps both of them feel better about the learning experiences.…”
Section: Discussionmentioning
confidence: 80%
“…Akin to past studies (Liao & Wang, 2015;Nosratinia & Abdi, 2017;Tang, 2016;Zarrinabadi & Rezazadeh, 2020) which found that strictly student-student interaction was not enough to reduce learner anxiety, students in these studies also expressed wanting more support and guidance from the teacher. Students in both studies also felt anxious and overwhelmed by the amount and difficulty of the activities, especially those that were completed pre-or postreading, much like the students expressed in Brantmeier (2005).…”
Section: Discussionmentioning
confidence: 99%